Integración y migración : las Iglesias pentecostales en España - Paola García (Les Cahiers ALHIM)
From the early eighties Spain has received immigrants that have slowly joined and integrated the Spanish society. The Latin Americans, who constitute the most important foreign group in Spain, have developed multiple forms of integration, one of which is their insertion in different Pentecostal churches. On the basis of the ethnographic information gathered in diverse field research (2004-2008), our aim is to show the efficiency of these institutions in the social and professional integration of the Latin American immigrants who live in Madrid.